Evaluation of oral potentially malignant disorders with autoflorescence, reflectance spectroscopy and vital staining and their correlation with histopathology – Hospital based prospective study. (July 2021) - Sharma, Deepa; Rimal, Jyotsna; Kumar Maharjan, Iccha; Shrestha, Ashish; Shrestha, Ashish; Regmee, Pragya
Highlights: Oral cancer is the sixth most common malignancy worldwide and is diagnosed at an increasing rate. OSCC affects the oral cavity and accounts for 90% of oral cavity cancers. OSCC is frequently preceded by OPMDs. Early detection of OPMDs is the most effective method for improving patient survival and decreasing mortality. Screening of OPMDs can aid to identify proper biopsy site, most likely to contain dysplasia or carcinomatous changes. Oral Screening thereby aids in early diagnosis of oral cancer and address its associated morbidities and mortalities. Abstract: Objectives: To evaluate diagnostic efficacy of Identafi® and toluidine blue in screening of Oral Potentially Malignant Disorders (OPMDs). Materials and methods: Forty nine patients (63 lesions) with OPMDs visiting Department of Oral Medicine and Radiology, B.P.Koirala Institute of Health Science (BPKIHS) were included in the study. After thorough history and oral examination, screening was done by Identafi® followed by toluidine blue staining. Then incisional biopsy under local anesthesia was performed from the site showing positive change followed by histopathological examination. Results: The overall sensitivity and specificity of Identafi® ' s violet light was 73% and 46.2%. The overall sensitivity and specificity of Identafi® ' s green-amber light were 78.4% and 15.4% respectively. The overall sensitivity and specificity of toluidine blue were 51.4 and 84.6 respectively. A statistically-significant association was observed between the toluidine blue and histopathology results, (p = 0.04), p value set at ≤ 0.05. Conclusion: Identafi®'s violet light and green amber light are more sensitive in detecting true positives. Toluidine blue is highly specific in ruling out true negative cases. The screening of OPMDs will help in selecting proper biopsy site followed by early diagnosis and intervention, hence increasing the prognosis, outcome and decrease complications associated with it.